UTILIZING QUESTIONING TECHNIQUE TO IMPROVE THE STUDENTS’ COMPREHENSION SKILLS ON EXPOSITORY TEXTS - Heri Hidayatullah (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2016)
This collaborative classroom action research (CAR) which was assembled in two cycles aimed at describing the implementation of questioning technique in improving the students’ comprehension skills on expository text. The procedures of instruction involve four steps namely (1) explaining and brainstorming; (2) grouping and discussing; (3) leading; and (4) concluding and presenting. The finding which supported by data on the teaching-learning process shows that the percentage of the students who get greater than or equal to 20 point at the first test is 59.5 % and 80 % in the second test. Accordingly, with 70 % of the participants get 20 point in the set-up criteria of success, it concluded that such technique is still outstanding in improving the students’ comprehension skills on expository texts type.